PAROXYSMAL SUPRAVENTRICULAR TACHYCARDIA: DIAGNOSIS, EMERGENCY CARE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Paroxysmal tachycardia is an attack of sharply rapid heartbeat with a heart rate from 130 to 200 or more per minute. Usually, the attack begins suddenly and also ends suddenly. The duration of the attack is from several seconds to several hours and days. With paroxysmal tachycardia, a focus of excitation appears in any part of the conduction system of the heart, generating electrical impulses of high frequency. Such a focus can occur in the cells of the conduction system of the atria or ventricles.